2010
DOI: 10.1111/j.1439-0388.2010.00857.x
|View full text |Cite
|
Sign up to set email alerts
|

Random regression models to estimate genetic parameters for test‐day milk yield in Brazilian Murrah buffaloes

Abstract: The objective of this work was to estimate covariance functions for additive genetic and permanent environmental effects and, subsequently, to obtain genetic parameters for buffalo's test-day milk production using random regression models on Legendre polynomials (LPs). A total of 17 935 test-day milk yield (TDMY) from 1433 first lactations of Murrah buffaloes, calving from 1985 to 2005 and belonging to 12 herds located in São Paulo state, Brazil, were analysed. Contemporary groups (CGs) were defined by herd, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
30
4
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 36 publications
10
30
4
3
Order By: Relevance
“…Additive genetic variances had the highest values in the early weeks of lactation, whereas permanent environmental variances were the highest in the twenty-fifth week (Figure 2). Likewise, Sesana et al (2010) compared different structures of permanent environmental variances using RRM and found higher variance estimates at early lactation in milking buffalo. Madad et al (2013b), using RRM in dairy buffalo, also reported high additive genetic variance in the early months of lactation, despite observing lower variances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additive genetic variances had the highest values in the early weeks of lactation, whereas permanent environmental variances were the highest in the twenty-fifth week (Figure 2). Likewise, Sesana et al (2010) compared different structures of permanent environmental variances using RRM and found higher variance estimates at early lactation in milking buffalo. Madad et al (2013b), using RRM in dairy buffalo, also reported high additive genetic variance in the early months of lactation, despite observing lower variances.…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypic variance estimates were higher during the first two weeks of lactation, which decreased at the ninth week and then reached the maximum value at the thirteenth week of lactation. Based on the results of Bignardi et al (2009) and Sesana et al (2010), Figure 2. Additive genetic (A), permanent environmental (B), phenotypic (C), and residual (D) variance estimates for test-day milk yield for each week of lactation of Khuzestan buffalo, obtained with a model with nine classes of heterogeneous residual effect and orders of fit for direct additive and permanent environmental effects equal to 3.…”
Section: Resultsmentioning
confidence: 99%
“…Negative genetic correlations for milk yield between the DIM 270 and DIM 90-180 were obtained in this study. Sesana et al (2010) reported about unexpected negative genetic correlation estimates between TDMY records in the first weeks with records from the middle to the end of lactation. Except for DIM 30 and DIM 60, the genetic correlations were higher in the initial test-day yield and decreased when the test-day interval was increased.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of records has shown in table 1. Residual variances were modeled via a step function with the following classes: 1, 3 (1-8, 9-12 and 13-32 weeks) (SESANA et al, 2010).…”
Section: Animals and Datamentioning
confidence: 99%